CARBONATE FACIES AND DIAGENETIC ANALYSIS PEUTU FORMATION ABC FIELD NORTH SUMATERA BASIN - SUPRIANTO, BAMBANG
ABC Field is a gas field located in North Sumatera Basin which have a significant reserves from carbonate reservoir Peutu Formation. The problem related to carbonate reservoir is the heterogeneity of reservoir quality, and if we don’t pay attention regarding these matter, it will resulted a failure on hydrocarbon exploitation. Reservoir quality especially porosity most influenced by carbonate facies distribution and diagenetic process followed. The research have been conducted to know the facies distribution and diagenetic developments on carbonate reservoir Peutu Formation in North Sumatera Basin, also the relationship to the ABC Field porosity development. The name and coordinates of the ABC Field are not published because it still not a public domain. The research resulted a close relationship between diagenetic process and porosity developments in carbonate reservoir Peutu Formation, but the facies distribution not so affected to the porosity development. It assumed happen because the carbonate reservoir in ABC Field have exposed to surface and become karst, but then subside so the porosity developed have been covered by cements and remained a little porosity. One thing that can destroy the developed porosity is a late charging of hydrocarbon to the rocks. The porosity rose again after a tectonic process occur in ABC Field so the pore become connected each other by a micro fracture. This affected a better porosity at any well that close to the fault zone.